2019
DOI: 10.1007/978-3-030-11395-7_38
|View full text |Cite
|
Sign up to set email alerts
|

Information Flows at Inter-team Boundaries in Agile Information Systems Development

Abstract: I nfo r m a tio n flow s a t in t e r-t e a m b o u n d a ri e s in a gil e info r m a tio n sy s t e m s d e v elo p m e n t R a hy, S a n d B a s s, J h t t p:// dx. d oi.o r g/ 1 0. 1 0 0 7/ 9 7 8-3-0 3 0-1 1 3 9 5-7_3 8 Ti t l e Info r m a tio n flow s a t in t e r-t e a m b o u n d a ri e s in a gil e info r m a tio n sy s t e m s d ev elo p m e n t A u t h o r s R a hy, S a n d B a s s, J Typ e Co nf e r e n c e o r Work s h o p It e m U RL This ve r sio n is a v ail a bl e a t : h t t p:// u sir.s alfo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Most of the research on communication within software engineering is found within the context of large-scale development, in particular global software engineering (Herbsleb and Moitra 2001;Avritzer et al 2010;Stapel and Schneider 2014) and/or agile software development (Yagüe et al 2016;Bjørnson et al 2018;Rahy and Bass 2019;Nundlall and Nagowah 2020). Existing research within this field, to a large extent primarily focuses on coordination with the general aim of organising software development projects in a way that decreases the need of coordination especially between sites and distant teams, and thereby minimising the need for communication across distances while maximizing communication within teams (Avritzer et al 2010).…”
Section: Inter-team Communicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the research on communication within software engineering is found within the context of large-scale development, in particular global software engineering (Herbsleb and Moitra 2001;Avritzer et al 2010;Stapel and Schneider 2014) and/or agile software development (Yagüe et al 2016;Bjørnson et al 2018;Rahy and Bass 2019;Nundlall and Nagowah 2020). Existing research within this field, to a large extent primarily focuses on coordination with the general aim of organising software development projects in a way that decreases the need of coordination especially between sites and distant teams, and thereby minimising the need for communication across distances while maximizing communication within teams (Avritzer et al 2010).…”
Section: Inter-team Communicationmentioning
confidence: 99%
“…For co-located software engineering, the research related to communication is mainly within large-scale agile software development and on coordinating multiple selfgoverning teams (Paasivaara et al 2012;Bjørnson et al 2018) including knowledge networks (Šmite et al 2017), and softer aspects such as common values and norms (Nyfjord et al 2014;Paasivaara et al 2014). Research specifically on inter-team communication within software engineering is sparse with the exception of work on knowledge and information flow between teams (Santos et al 2015;Rahy and Bass 2019).…”
Section: Inter-team Communicationmentioning
confidence: 99%
See 3 more Smart Citations